2008
DOI: 10.1007/s10298-008-0346-7
|View full text |Cite
|
Sign up to set email alerts
|

Composition chimique et activité antimicrobienne des huiles essentielles de Thymus capitatus et de Thymus bleicherianus du Maroc

Abstract: Ce travail vise l'étude de l'activité antibactérienne et antifongique et de la composition chimique des huiles essentielles de Thymus capitatus et de Thymus bleicherianus du Maroc. Les échantillons de Thymus capitatus ont fourni le rendement le plus élevé : 2,05 % contre 1,75 % pour Thymus bleicherianus. Les analyses chromatographiques (CG et CG/SM) ont montré que l'huile essentielle de Thymus capitatus contient le carvacrol (70,92 %) comme constituant majoritaire et que celle de Thymus bleicherianus est domin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
3
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 30 publications
4
34
3
2
Order By: Relevance
“…Camphor was the predominant compound in the sample of Aflou (Laghouat) with a percentage of 17.68%, this content agrees with the results of Amarti et al [26] and Zouari et al [27] who have detected camphor as major compound for T. algeriensis from Morocco and Tunisia, respectively. The sample of Djelfa was predominantly composed of -terpinenyle acetate (27.32%), a compound completely absent in the sample of Aflou.…”
Section: Essential Oil Yield and Chemical Compositionsupporting
confidence: 81%
See 1 more Smart Citation
“…Camphor was the predominant compound in the sample of Aflou (Laghouat) with a percentage of 17.68%, this content agrees with the results of Amarti et al [26] and Zouari et al [27] who have detected camphor as major compound for T. algeriensis from Morocco and Tunisia, respectively. The sample of Djelfa was predominantly composed of -terpinenyle acetate (27.32%), a compound completely absent in the sample of Aflou.…”
Section: Essential Oil Yield and Chemical Compositionsupporting
confidence: 81%
“…Indeed, Dob et al identified for a sample of T. algeriensis (Medea -Algeria) the following major compounds: linalool (47.30%), thymol (29.20%) and p-cymene (6.80%) [57]; While Hazzit et al have suggested the existence of two chemotypes (samples were collected from the Chrea National Park, and the Chlef regions); the first was characterized by terpinyl acetate (18.00%), trans-nerolidol (12.60%), -pinene (11.10%), borneol (9.00%) and bornyl acetate (7.70%), while the second has presented the following major compounds: terpinen-4-ol (10.60%), camphor (10.10%), p-cymene (9.90%), -pinene (6.50%) and 1,8-cineole (6.50%) [42]. Comparing the founding of these In a matter of fact, the difference in composition of the EOs of T. algeriensis might be due to several factors, such as climate, season of harvest, stage of development and even genetic profiles of the species [26,50,[58][59][60].…”
Section: Essential Oil Yield and Chemical Compositionmentioning
confidence: 99%
“…Ce genre possède plusieurs activités biologiques comme antispasmodique (Meister et al, 1999), antimicrobien (Essawi & Srour, 2000 ;Amarti et al, 2008Amarti et al, , 2010, expectorant (Brasseur, 1983), antioxydant (Miura & Nakatami, 1989 ;Vardar-Ünlü et al, 2003 ;Sokmen et al, 2004 ;Bouhdid et al, 2006 ;Hazzit et al, 2009 ;Safaei-Ghomi et al, 2009) et anti-inflammatoire (Ismaili et al, 2001(Ismaili et al, , 2002. Au Maroc, il ya vingt et une espèces de thym (Benabid, 2000), parmi lesquelles T. capitatus, T. algeriensis, T. ciliatus et T. bleicherianus.…”
Section: Introductionunclassified
“…The major class, the oxygenated monoterpenes (88.50%), was mainly represented by thymol (71.45%) followed by linalool (7.89%) and carvacrol (3.98%). In this case, we found that the literature reports a comparable carva- crol yield in Thymus algeriensis as well as in other Thymus species (7,10,11). However, our oil is characterized by a very high content of thymol.…”
Section: Essential Oil Characterizationmentioning
confidence: 45%
“…Identification was confirmed by comparison of their mass spectral fragmentation patterns with those stored in the MS database (National Institute of Standards and Technology and Wiley libraries) and with mass spectra literature data (5,6) and identification data reported by Amarti et al (7). Component relative concentrations were obtained directly from GC peak areas.…”
Section: Analysis Of the Essential Oilmentioning
confidence: 99%